Analisis Efikasi Diri Santri dalam Pembelajaran IPS - Putri, Dinti Susanti (IJOCE: Indonesia Journal of Civic Education, 2026)
This study aims to analyze students' self-efficacy in learning Social Studies (IPS) at MTs Pancasila, Bengkulu City. The research method used was descriptive qualitative, with data collected through interviews, observation, and documentation. The results indicate that students' self-efficacy is still relatively low, influenced by internal factors such as experiences of failure and lack of self-confidence, as well as external factors such as social support and the learning environment. In conclusion, students' self-efficacy is still relatively low. This is reflected in their lack of self-confidence and lack of active involvement in learning activities.   Keywords: Modernization, Tradition, Berinai Curi, Keban Agung, Seluma